2014
DOI: 10.1111/j.1948-7134.2014.12069.x
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito communities with trap height and urban-rural gradient in Adelaide, South Australia: implications for disease vector surveillance

Abstract: Understanding the factors influencing mosquito distribution is important for effective surveillance and control of nuisance and disease vector mosquitoes. The goal of this study was to determine how trap height and distance to the city center influenced the abundance and species of mosquitoes collected in Adelaide, South Australia. Mosquito communities were sampled at two heights (<2m and ~10m) along an urban-rural gradient. A total of 5,133 mosquitoes was identified over 176 trap nights. Aedes notoscriptus, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 45 publications
5
19
0
Order By: Relevance
“…This finding is supported by studies across Australia which have found that RRV infection rates (human and mosquito) vary at a relatively small scale [4,[35][36][37]. The fine-scale variation in disease rates we see here could be due to variation in reporting/testing by medical practitioners, behavioural differences of the patients or could represent variation in transmission ecology [19,34]; potentially all three factors are influencing disease rates to some degree. The fine-scale variation in disease rates we see here could be due to variation in reporting/testing by medical practitioners, behavioural differences of the patients or could represent variation in transmission ecology [19,34]; potentially all three factors are influencing disease rates to some degree.…”
Section: Using Landscan To Improve Map Interpretationsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is supported by studies across Australia which have found that RRV infection rates (human and mosquito) vary at a relatively small scale [4,[35][36][37]. The fine-scale variation in disease rates we see here could be due to variation in reporting/testing by medical practitioners, behavioural differences of the patients or could represent variation in transmission ecology [19,34]; potentially all three factors are influencing disease rates to some degree. The fine-scale variation in disease rates we see here could be due to variation in reporting/testing by medical practitioners, behavioural differences of the patients or could represent variation in transmission ecology [19,34]; potentially all three factors are influencing disease rates to some degree.…”
Section: Using Landscan To Improve Map Interpretationsupporting
confidence: 82%
“…The scale at which RRV risk operates in SA is unknown but different RRV ecologies exist across the state [28] and vector and virus prevalence appears to vary at the scale of kilometres [34]. The scale at which RRV risk operates in SA is unknown but different RRV ecologies exist across the state [28] and vector and virus prevalence appears to vary at the scale of kilometres [34].…”
Section: Using Landscan To Improve Map Interpretationmentioning
confidence: 99%
“…The case of Ae. camptorhynchus is quite different: its ecology is restricted to coastal areas, or around inland brackish zones [49], with a lower abundance in urban areas [50], with local exceptions in suburb areas around Melbourne, Victoria (SL, pers. Comm.).…”
Section: Discussionmentioning
confidence: 99%
“…quiquefasciatus were caught in traps set at least 8m off the ground, whilst a higher abundance of Ae. vigilax were found in traps 1.5m off the ground, for the same locations [47, 48]. In our meta-analysis, Cx.…”
Section: Discussionmentioning
confidence: 76%